The Role of Phospholipase D and MAPK Signaling Cascades in the Adaption of Lichen Microalgae to Desiccation: Changes in Membrane Lipids and Phosphoproteome. - Gasulla, Francisco; Barreno Rodríguez, Eva; López Parages, María; Cámara, J.; Jiménez-Gámez, Carlos; Dörmann, Peter; Bartels, Dorothea (Oxford University Press, 2016)
Classically, lichen phycobionts are described as poikilohydric organisms able to undergo desiccation due to the constitutive presence of molecular protection mechanisms. However, little is known about the induction of cellular responses in lichen phycobionts during drying. The analysis of the lipid composition of the desiccated lichen microalga Asterochloris erici revealed the unusual accumulation of highly polar lipids (oligogalactolipids and phosphatidylinositol), which prevents the fusion of membranes during stress, but also the active degradation of cone-shaped lipids (monogalactosyldiacylglycerol and phosphatidylethanolamine) to stabilize membranes in desiccated cells. The level of phosphatidic acid increased 7-fold during desiccation, implicating a possible role for phospholipase D (PLD) in the response to osmotic stress. Inhibition of PLD with 1-butanol markedly impaired the recovery of photosynthesis activity in A. erici upon desiccation and salt stress (2M NaCl). These two hyperosmotic stresses caused the phosphorylation of c-Jun N-terminal kinase (JNK) and p38-like mitogen-activated protein kinase (MAPK) and the dephosphorylation of extracellular signal-regulated kinase (ERK). The incubation with 1-butanol reduced the phosphorylation of JNK-like proteins and increased the dephosphorylation of ERK-like proteins, which indicates an upstream control of MAPK cascades by PLD. The phosphoproteome showed that desiccation caused the phosphorylation of several proteins in A. erici, most of them involved in protein turnover. The results demonstrate that lichen phycobionts possess both constitutive and inducible protective mechanisms to acquire desiccation tolerance. Among others, these responses are controlled by the PLD pathway through the activation of MAPK cascades.
https://academic.oup.com/pages/self_archiving_policy_b
Keywords: Líquenes - Aspectos moleculares; Asterochloris erici; Desiccation tolerance; Lipid; MAPK; Phospholipase D; Phosphoproteome